EFEKTIVITAS REKRUTMEN ONLINE DALAM MENARIK KANDIDAT SISWA BERKUALITAS DI MADRASAH ALIYAH AL HIKMAH BANDAR LAMPUNG - Dessy Nofita Sari; Yetri Yetri; Oki Dermawan; Riyuzen Praja Tuala (Jurnal Manajemen Pendidikan, 2026)
The development of digital technology has encouraged educational institutions to utilize online-based systems in the student admission process. The implementation of online recruitment is expected to improve the effectiveness of student admissions through easier access, wider dissemination of information, and more efficient administrative management. This study aims to analyze the effectiveness of online recruitment in attracting qualified student candidates at Madrasah Aliyah Al-Hikmah Bandar Lampung. The research employed a qualitative approach with a descriptive research design. Data were collected through observation, semi-structured interviews, and documentation involving the admission committee, new students, and parents. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation. The results indicate that online recruitment increases the number of applicants, accelerates administrative processes, and improves cost efficiency through the use of digital media. However, the quality of applicants is still determined through a selection process based on the academic and religious standards established by the madrasah.